Pengaruh Tingkat Hutang, Intensitas Aset Tetap dan Ukuran Perusahaan terhadap Manajemen Pajak (Studi Empiris pada Perusahaan Pertambangan di BEI Periode 2019-2023) - Dewi, Sri; Romadhina, Anggun Putri (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The mining sector significantly contributes to Indonesia’s tax revenue but remains highly volatile due to global commodity price fluctuations and fiscal policy changes. This study addresses the inconsistency in prior research findings regarding the effect of financial factors on tax management, particularly in capital intensive industries. The objective is to examine whether debt level, fixed asset intensity, and firm size influence tax management among 17 mining companies listed on the Indonesia Stock Exchange during 2019-2023. A quantitative approach with panel data regression was employed, using the common effect model selected through Chow, Hausman, and Lagrange Multiplier tests. Tax management was proxied by the effective tax rate (ETR), while independent variables were measured by debt-to-equity ratio, capital intensity, and firm size (natural log of total assets). The findings indicate that, simultaneously, the three variables significantly affect tax management, explaining 89.9% of its variation. However, none of the variables show a significant partial effect. These results suggest that tax strategies in the mining sector are shaped more by the interaction of multiple financial factors rather than by single determinants. The study contributes to the literature by highlighting the importance of an integrated approach to tax management in industries exposed to market volatility.